Foreign Trade in Agricultural Products between Poland and Ukraine in the Context of the Development of International Economic Integration - Kryvenko, Nadiia (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2024)
The economic development of countries is largely determined by their foreign trade. Poland’s trade with Ukraine is facilitated by many years of experience, proximity and the influence of international economic integration. Both countries are large producers and exporters of agri-food products, and there is a prospect of deepening relations in the context of developing integration processes. The importance of this study stems from Ukraine’s aspirations for European integration, Poland’s membership in the EU and the development of trade relations with Ukraine over the years. At the same time, the main issues remain: access to EU markets, harmonisation of product quality standards, trade liberalisation in the context of deepening integration, non-discrimination of countries and so forth. The purpose of the study is to determine the prospects for the development of trade in agricultural products between Poland and Ukraine in the context of international economic integration, identify the most promising areas of integration, assess the importance of agricultural products in foreign trade and analyse the trends in their foreign trade. The study utilises the scientific works of researchers, statistical data from international trade statistics for 2003-2022 and general scientific and specific research methods, including methods of analysis and synthesis, statistical analysis, abstract-logical and system analysis, generalisation and others. Exports from Poland and Ukraine are increasing, with Poland’s exports rising more significantly. The share of agri-food products, especially those from Ukraine, is growing. Ukrainian exports of agri-food products to Poland have increased more than total exports. The influence of international economic integration on foreign trade is evident; following the agreement between Ukraine and the EU, Poland’s trade with Ukraine has increased. A similar trend is observable in the trade between these countries and the EU. Foreign trade between the countries is growing; the trade balance between Poland and Ukraine for all products is positive, but for agri-food products it has become negative. The EU is the main importer for Poland. The commodity structure of Poland is more diversified than that of Ukraine. The types of products for which it is desirable to establish common production and mutual trade have been identified in order to provide the population with quality products at an affordable price and expand their position in the world market. Product groups with the greatest prospects for integration, particularly in trade, between Poland and Ukraine have been identified. According to calculations based on dynamic series, it is assumed that the trend in the development of trade in agricultural products between the countries will continue in the future, which could contribute to effective integration between them. Thus, international economic integration aids the development of foreign trade between Poland and Ukraine, as well as between Ukraine and the EU. Ukraine needs to promote export diversification as it significantly lags behind Poland – which should contribute to an increase in exports. It is necessary to stimulate the overall production and export of selected types of agricultural and food products, which should help enhance product competitiveness, improve quality, increase the income of producers and enable both countries to expand their positions in the EU and global markets. This is particularly important in the context of developing international economic integration, the availability of natural resources in Poland and Ukraine, the increase in global demand for food and the deepening climate crisis. The issue is even more pressing since Ukraine is in a difficult situation under martial law, yet it remains an important trading partner in the global market.